Analysis of Cow-Calf Microbiome Transfer Routes and Microbiome Diversity in the Newborn Holstein Dairy Calf Hindgut - Zhu, Huan; Yang, Minna; Loor, Juan J.; Elolimy, Ahmed; Li, Lingyan; Xu, Chuang; Wang, Weidong; Yin, Shuxin; Qu, Yongli (Frontiers in Nutrition, 2021)
Hindgut microorganisms in newborn calves play an important role in the development of immunity and metabolism, and optimization of performance. However, knowledge of the extent to which microbiome colonization of the calf intestine is dependent on maternal characteristics is limited. In this study, placenta, umbilical cord, amniotic fluid, colostrum, cow feces, and calf meconium samples were collected from 6 Holstein cow-calf pairs. Microbial composition was analyzed by 16S rRNA gene high-throughput sequencing, and maternal transfer characteristics assessed using SourceTracker based on Gibbs sampling to fit the joint distribution using the mean proportions of each sample with meconium as the “sink” and other sample types as different “sources”. Alpha and beta diversity analyses revealed sample type-specific microbiome features: microbial composition of the placenta, umbilical cord, amniotic fluid, colostrum, and calf feces were similar, but differed from cow feces (p<0.05). Compared with profiles of meconium vs. placenta, meconium vs. umbilical cord, and meconium vs. colostrum, species differences between the meconium and amniotic fluid were most obvious. SourceTracker analysis revealed that 23.8 ± 2.21% of the meconium OTUs matched those of umbilical cord samples, followed by the meconium-placenta pair (15.57 ± 2.2%), meconium-colostrum pair (14.4 ± 1.9%), and meconium-amniotic fluid pair (11.2 ± 1.7%). The matching ratio between meconium and cow feces was the smallest (10.5 ± 1%). Overall, our data indicated that the composition of the meconium microflora originated from multiple maternal sites including umbilical cord, placenta, colostrum, and amniotic fluid. The umbilical cord microflora seemed to contribute the most to colonization of the fecal microflora of calves. Bacteria with digestive functions such as cellulose decomposition and rumen fermentation were mainly transmitted during the maternal transfer process.